(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In this article studied the advantages and implementation stages of modular educational technology in the training of professional education teachers. The difference of modular teaching from other teaching technologies is as follows: educational content is presented in the form of complete, independent modules; the teacher’s communication with the student is carried out on a new basis.